Rede de Cuidado da Saúde Mental: tecendo práticas de inclusão social no município de Campina Grande-PB. - Azevedo, Elisângela Braga de (2010)
The current mental health care network, represented by substitutes services for psychiatric hospital, is a strategy for changing the hospital centered model for the community. These services operate from the perspective of promoting the rehabilitation of people suffering mental work, in education, recreation, society, among other sectors, encouraging the rehabilitation or construction of citizenship. This study investigated the practices of social inclusion developed by mental health care network professionals for people suffering psychological distress in view of the progress made with implementation of psychiatric reform in Campina Grande PB. This is a descriptive research qualitative interpretive approach, conducted with 19 professionals who work in the care of mental health. The empirical data were obtained through semi structured interview, during June July 2010. The data analysis was based on the technique of content analysis categorical theme proposed by Bardin, which resulted in three thematic units: design professionals on social inclusion, social inclusion practices: encouraging intersectoral and comprehensive care in mental health and, strategies managerial policies that facilitate and hinder the promotion of inclusive practices in the mental health care network. This study suggests a reflection on the different practices that have been conducted in the municipality and make visible advances occurring toward the consolidation of the psychiatric reform. The practices identified favored the linkage between mental health and other sectors of society, is education, culture, economy, creating social networks. Were identified as weaknesses to overcome the shortage of financial and material resources and social, institutional and professional prejudice for the mentally ill. The facilitating factors for the advancement of reform were highlighted: the interdisciplinary work, intersectoral collaboration and support of municipal mangers to train teams who work in psychosocial care, in primary care and other sectors of the care network. It is concluded that the council has made progress in psychiatric reform and has been consolidating the community mental health model, despite the obstacles which still persist, but can be overcome.